2023
DOI: 10.3390/ijms241310813
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin Modulates Osteogenic Commitment in Human Adipose-Derived Stem Cells

Abstract: Human adipose-derived stem cells (hASCs) are commonly harvested in minimally invasive contexts with few ethical concerns, and exhibit self-renewal, multi-lineage differentiation, and trophic signaling that make them attractive candidates for cell therapy approaches. The identification of natural molecules that can modulate their biological properties is a challenge for many researchers. Oxytocin (OXT) is a neurohypophyseal hormone that plays a pivotal role in the regulation of mammalian behavior, and is involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
1
2
0
Order By: Relevance
“…Consistent with our study, they showed that OT increases the gene expression of DSP, Wnt10a, and BGP in dental pulp stem cells.In their review study, Liu Feixiang et al(Feixiang, Yanchen et al 2023) showed that OT can stimulate osteoblast mineralization by promoting translocation of the OT receptor to the osteoblast nucleus.Additionally, by inducing intracellular Ca 2+ release and nitric oxide synthesis, OT can regulate the OPG/RANKL ratio in osteoblasts and exert a two-way regulatory effect on osteoclasts. It can also increase osteocyte and chondrocyte activity, which increase bone mass and improve bone microstructure.The present study's ndings align with previous research, indicating that OT promotes the differentiation of stem cells into osteoblasts(Elabd, Basillais et al 2008, Petrocelli, Abruzzo et al 2023).…”
supporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with our study, they showed that OT increases the gene expression of DSP, Wnt10a, and BGP in dental pulp stem cells.In their review study, Liu Feixiang et al(Feixiang, Yanchen et al 2023) showed that OT can stimulate osteoblast mineralization by promoting translocation of the OT receptor to the osteoblast nucleus.Additionally, by inducing intracellular Ca 2+ release and nitric oxide synthesis, OT can regulate the OPG/RANKL ratio in osteoblasts and exert a two-way regulatory effect on osteoclasts. It can also increase osteocyte and chondrocyte activity, which increase bone mass and improve bone microstructure.The present study's ndings align with previous research, indicating that OT promotes the differentiation of stem cells into osteoblasts(Elabd, Basillais et al 2008, Petrocelli, Abruzzo et al 2023).…”
supporting
confidence: 92%
“…In the Petrocelli et al (Petrocelli, Abruzzo et al 2023) study examining the effect of OT on the proliferation of adipose-derived stem cells, although OT had no cytotoxic effects on the cells, no proliferative effect was found by this agent. They showed that the expression of genes involved in cell proliferation and cell cycle including MKI67, CCND1, CDKN2A, CDKN1A, and TP53, was not affected in OT-treated cells.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation